Integrated biosystems in the co-digestion of crude glycerol in agro-industrial wastes for the H-2 and CH4 generation - Rodrigues, Caroline Varella [UNESP]; Adames, Luan Vieira [UNESP]; Costa Marques, Rodrigo Fernando [UNESP]; Jacobus, Ana Paula [UNESP]; Pires, Lorena Oliveira [UNESP]; Maintinguer, Sandra Imaculada [UNESP] (Univ Fed Rio De Janeiro, Lab Hidrogenio, 2021)
The biodiesel production has grown and it gained prominence in the global energy scenario. As a result, its main co-product, crude glycerol (CG), has accompanied this increase, causing the formation of large stocks of this residue. A promising alternative for its reduction is the use by anaerobic biological processes aiming at the biogas production, as hydrogen (H-2) as methane (CH4). It is known that the efficiency of this bioconversion increases through co-digestion with other organic waste. Thus, the objective of this study consisted in the co-digestion of CG, from the biodiesel production through waste cooking oils, with citrus vinasse (CV), in two sequential stages. In the 1st stage (Assay 1), the anaerobic reactor was operated in batch, fed with 5 g COD L-1 CG and 5 g COD L-1 CV, in the presence of a mixed culture belonging to the genus Clostridium sp., at 37 degrees C, pH 5.5, headspace with N-2, generating 4.48 mmol H2 L-1 in 112 h of experiment, being consumed 93.19 % of CG and 74.00 % of glucose. A control assay (Control 1) was assembled with only 5 g COD L-1 CG, without H-2 production. The effluent generated in Assay 1 (200 mL) was used as a substrate in the 2nd stage (Assay 2) by an inoculum in natura identified by a consortium of anaerobic bacteria and methanogenic archaea, in the anaerobic methanogenic reactor (500 mL), headspace with N-2, pH 7.0, at 37 degrees C, generating 229.08 mmol CH4 L-1 in 624 h of operation. In addition, 87.34 % of COD and 93.75 % of methanol from CG were consumed. The effluent generated by Control 1 produced only 40.58 mmol CH4 L-1 (Control 2). Thus, it was found that co-digestion increased the biogas generation, with consumption of organic and toxic waste present in CG through integrated systems.
Keywords: Anaerobic digestion; Biodiesel; Hydrogen; Methane